PENGARUH PENAMBAHAN EKSTRAK JAHE TERHADAP KUALITAS ES KRIM DADIAH - Astuti, Sri Puji; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was motivated by the utilization of gingger extract which cansubstract of acid and a less favorable flavour at dadiah does not liked by somepeoples. The aims of this research was to analyzed the influence of added of thegingger extract as much as 3%, 6%, and 9% from the milk in used to the qualityof color, aroma, taste and texture. This type of research was a true experimentconducted in April-may 2017 and located in the culinary workshop HomeEconomic, Faculty of Tourism and Hospitality, State University of Padang.Instrument used was organoleptic test with level test, hedonic test and examinehypotheses used statistics ANAVA and if there was different, continued withDuncan Test. The result of research showed that there was a real influence inadded of gingger extract as much as 3%, 6%, and 9% to the quality of aroma andtaste from dadiah ice cream, while for the quality of the color, texture andhedonic test there was not a real difference influence. The best results based onthe organoleptic test are found in 3%.Keywords: Extract Gingger, Ice Cream, Quality